Reproductive and developmental toxicity of carbon-based nanomaterials: A literature review. Issue 4 (20th April 2016) - Ema, Makoto; Hougaard, Karin Sørig; Kishimoto, Atsuo; Honda, Kazumasa
Abstract: We summarized the findings of reproductive and developmental toxicity studies on carbon-based nanomaterials (CNMs). Placental transfer of fullerenes in rats and single-walled (SW) and multi-walled (MW) CNTs in mice was shown after intravenous injection. SWCNTs appeared to be embryolethal and teratogenic in mice when given by intravenous injection and induced death and growth retardation in chicken embryos. In mice-administered MWCNTs, fetal malformations after intravenous and intraperitoneal injections and intratracheal instillation, fetal loss after intravenous injection, behavioral changes in offspring after intraperitoneal injection, and a delay in the delivery of the first litter after intratracheal instillation were reported. Oral gavage of MWCNTs had no developmental toxicity in mice and rats. MWCNTs produced morphological defects, developmental arrest, and death in zebrafish embryos. Intratracheal instillation of carbon black (CB) induced testicular toxicity in adult mice. Maternal airway exposure to CB in gestation had testicular toxicity and altered postnatal behavior, renal development, immune and genotoxic responses, and brain morphology in mouse offspring. Nanodiamonds and graphite nanoparticles inhibited vasculogenesis and/or angiogenesis in chicken embryos. Graphene oxide (GO) induced malformations in zebrafish embryos. Intravenous injection of reduced GO during late gestation caused maternal death and abortion in mice. Oral administration of GO during lactation caused growth retardation of offspring. Overall, the available data provide initial information on the potential reproductive and developmental toxicity of CNMs. However, confirmatory studies using well-characterized CNMs, state-of-the-art study protocol and appropriate route of exposure, are required to clarify the findings and provide information suitable for risk assessment.